Apxatas de difuntos en el altiplano aymara de Bolivia - Fernández Juárez, Gerardo (Revista Española de Antropología Americana, 2006)
The altars for defuncts, so-called apxatas, which are arranged for the All Saint’s Day in the Bolivian Aymara highlands, constitute a useful conceptual framework to the analysis of ritual ceremonies in this part of the Andes. In fact, All Saint’s Day is a very complex ceremony of a great anthropological interest to valorate the relevance of defuncts in the social life of contemporary Aymara communities.
Keywords: Aymara; Apxata; All Saint’s Day